The Commons Revisited: Revalorizing the Role of comuneiros in the Redesign of Urban Agro‐Food and Agroforestry Systems. Issue 1 (17th August 2017) - Dominguez Garcia, M. Dolores; Swagemakers, Paul; Schmid, Otto
Abstract : Continuing urbanization means that city regions face challenges of development, governance, and sustainability. One of these challenges relates to the management of urban green space, whether municipal parks, forests, or productive land (animal husbandry, vegetable or fruit production). This paper draws on case study research of forestry associations in Galicia. We pay specific attention to the role of comuneiros (commoners): parishioners, who collectively own and manage often‐neglected green spaces: planting or rejuvenating forests of native species to enhance ecological services (water retention, fire prevention, biodiversity) while also including productive functions such as forest fruit production and small‐scale animal husbandry. At the same time these activities create social benefits. With the aim of examining the position and strategies of self‐governing forest organizations, we explore the organizational‐institutional environment of the commons and how this facilitates (and/or obstructs) the objective of providing multiple sustainable and health benefits within the parishes, between them, and to nearby urban residents. We conclude that this particular type of management of urban green space provides products (food and non‐food) and services which are not only of private interest in that they create potential new business opportunities but also of high public value.